Selective Nickel-Catalyzed Conversion of Model and Lignin-Derived Phenolic Compounds to Cyclohexanone-Based Polymer Building Blocks - Schutyser, Wouter; Van den Bosch, Sander; Dijkmans, Jan; Turner, Stuart; Meledina, Maria; Van Tendeloo, Gustaaf; Debecker, Damien P.; Sels, Bert F. (ChemSusChem, 2015)
Valorization of lignin is essential for the economics of future lignocellulosic biorefineries. Lignin is converted into novel polymer building blocks through four steps: catalytic hydroprocessing of softwood to form 4‐alkylguaiacols, their conversion into 4‐alkylcyclohexanols, followed by dehydrogenation to form cyclohexanones, and Baeyer–Villiger oxidation to give caprolactones. The formation of alkylated cyclohexanols is one of the most difficult steps in the series. A liquid‐phase process in the presence of nickel on CeO2 or ZrO2 catalysts is demonstrated herein to give the highest cyclohexanol yields. The catalytic reaction with 4‐alkylguaiacols follows two parallel pathways with comparable rates: 1) ring hydrogenation with the formation of the corresponding alkylated 2‐methoxycyclohexanol, and 2) demethoxylation to form 4‐alkylphenol. Although subsequent phenol to cyclohexanol conversion is fast, the rate is limited for the removal of the methoxy group from 2‐methoxycyclohexanol. Overall, this last reaction is the rate‐limiting step and requires a sufficient temperature (>250 °C) to overcome the energy barrier. Substrate reactivity (with respect to the type of alkyl chain) and details of the catalyst properties (nickel loading and nickel particle size) on the reaction rates are reported in detail for the Ni/CeO2 catalyst. The best Ni/CeO2 catalyst reaches 4‐alkylcyclohexanol yields over 80 %, is even able to convert real softwood‐derived guaiacol mixtures and can be reused in subsequent experiments. A proof of principle of the projected cascade conversion of lignocellulose feedstock entirely into caprolactone is demonstrated by using Cu/ZrO2 for the dehydrogenation step to produce the resultant cyclohexanones (≈80 %) and tin‐containing beta zeolite to form 4‐alkyl‐ε‐caprolactones in high yields, according to a Baeyer–Villiger‐type oxidation with H2O2. In the Ni‐ck of time: The four‐step conversion of lignocellulose to caprolactones is demonstrated. One of the major challenges is the selective removal of the methoxy group from the guaiacols. Ni/CeO2 is a suitable catalyst for this reaction, yielding considerable amounts of cyclohexanols, which are prone to undergo dehydrogenation and Baeyer–Villager oxidation.